Topical Review: Optometric Considerations in Sports Versus E-Sports. Issue 3 (June 2022) - Argilés, Marc; Quevedo-Junyent, Lluïsa; Erickson, Graham
Electronic sports (e-sports) have recently emerged to become a rapidly growing form of videogame competition, requiring gamers to spend many hours in front of a visual display. The nature of this new modality raises important considerations for ocular health, and visual and perceptual functioning, compared to traditional sports. In general, sports performance has been associated with open spaces, gross motor movement, and balance, while electronic sports require visual and attentional stamina at near distances with fine motor control. From an optometric viewpoint, visual perception is specific to both the sports modality and the environment where sports take place. In this topical review, we consider e-sport optometric factors such as screen time and digital eyestrain, visual skill demands, and perceptual cognitive skills such as visual attention. We compare training considerations for traditional sports and training in gaming platforms, with recommendations for future research in this growing modality. The goal of this review is to raise awareness of the various elements to consider when providing vision care to e-sport participants.